Establishment of an efficient in vitro propagation protocol for Sumac (Rhus coriaria L.) and confirmation of the genetic homogeneity - Amiri, Saleh (Sci Rep, 2021)
The conventional reproduction methods are not efficient for regeneration of Sumac (Rhus coriaria L.). The purpose of this work was to study the micropropagation of R. coriaria using lateral buds as explant in Murashige and Skoog (MS) medium with different concentrations of plant growth regulator (PGRs). Four concentrations of Benzylaminopurine (BAP) in combination with three concentrations of indol-3-butyric acid (IBA) and 1.0 mg/L gibberellic acid (GA3) were tested for establishment and shoot multiplication. For root induction, IBA was used at four levels combined with 0, 0.5 and 1 mg/L of naphthalene acetic acid (NAA) in full and half strength of MS medium. BAP at 2 mg/L with 1 mg/L IBA was best, with 88.88% of establishment. The highest shoot proliferation (12.30 ± 0.30) was obtained in medium fortified with 2 mg/L BAP plus 0.5 mg/L IBA and the highest shoot length (8.50 cm) was obtained at 3 mg/L BAP plus 1 mg/L IBA. The highest rooting (100%) was observed in 1/2-strength MS medium containing 1 mg/L IBA with 0.5 mg/L NAA. In conclusion, an efficient protocol with high rate of proliferation and rooting is described for R. coriaria, which can be used in massive propagation.